Resin directional flow and degree of cure sensing using chirped optical fibre long period gratings - Wong, Rebecca Y. N.; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (IEEE, 2017)
The use of chirped long period gratings (CLPGs) for monitoring the flow, the direction of the flow and the subsequent cure of an epoxy resin is presented. The asymmetric properties of the CLPG and its sensitivity to refractive index changes were exploited to facilitate the measurement of the direction of the flow. The performances of a continuously chirped LPG (CCLPG) and a step chirped LPG (SCLPG) were compared, with the CCLPG showing improved spatial resolution. The CCLPG and SCLPG were also used to monitor changes in the refractive index of the resin during cure, with the results showing close agreement with measurements undertaken simultaneously using a fibre optic Fresnel refractometer.
Keywords: Fibre optics; optical fibre sensor; long period grating; chirped grating; directional flow; resin cure; Fresnel sensor